Intravenous iron therapy in non‐anemic iron‐deficient menstruating adolescent females with fatigue. Issue 10 (20th July 2016) - Sharma, Ruchika; Stanek, Joseph R.; Koch, Terah L.; Grooms, Linda; O'Brien, Sarah H.
Abstract : Menstruating women, with or without underlying bleeding disorders, are at increased risk for developing iron deficiency‐related fatigue, even in the absence of anemia. Oral iron therapy has limitations which include poor absorption and non‐adherence due to gastrointestinal side effects. We performed a prospective clinical trial of post‐menarchal adolescent females with iron‐deficiency with or without mild anemia and fatigue who received a standardized regimen of intravenous iron sucrose. The baseline mean (SD) hemoglobin was 11.96 g dl −1 (1.05) in 20 girls (ages 14–21 years); with a range of 10.3–14.1 g dl −1 . In this cohort, intravenous iron was well tolerated and patients demonstrated a sustained increase in ferritin levels with means (SD) of 13.4 ng ml −1 (13.1) at baseline to 141.5 ng ml −1 (104.5) at 6 weeks and 85.2 ng ml −1 (128.4) at 6 months after the infusions. We used a standardized (Peds QL TM Multidimensional) fatigue scale to objectively measure fatigue and proxy scores by parents with mean screening scores (SD) of 35.2 (16.8) and 31.9 (19.6), respectively. We demonstrated a clinically significant improvement both in patient as well as parent fatigue scores (in 19 out of 20 subjects) at 6 weeks (Mean (SD) 58.3 (21.3) [ P < 0.0001] and 57 (24.4) [ P < 0.0001], respectively); as well as 3 and 6 months after the iron infusions. In nonanemic patients, iron administration did not significantly influence hemoglobin concentration. Therefore, the fatigue‐reducing effects of iron therapy reflect the nonhematological functions of iron. Am. J. Hematol. 91:973–977, 2016. © 2016 Wiley Periodicals, Inc.